Hubungan Ketergantungan terhadap Pemberian Gift dengan Tingkat Percaya Diri Siswa Kelas 3 SDN Sidodadi 1/153 Surabaya - Frissenda Septrianur Marinda Karno Putri; Aura Nada Kamila; Andika Adinanda Siswoyo (Lembaga Yasin AlSys, 2025)
Dependence on gift-giving in the context of elementary education has become a significant issue with the potential to affect students' psychological development, particularly in terms of self-confidence. This study aims to analyze the influence of dependence on rewards on the self-confidence levels of third-grade students at SDN Sidodadi I/153 Surabaya. Employing a descriptive qualitative approach, data were collected through documentation studies, questionnaires, and direct observations of the students as the primary subjects. The findings indicate that appropriate reward-giving can enhance students' motivation and self-confidence; however, excessive dependence on rewards may hinder their initiative and independence. The forms of reward used include praise, recognition, physical gifts, and tokens of appreciation, which proved effective when administered proportionally and contextually. The study concludes that measured reward-giving can serve as an educational strategy in fostering students' character and self-confidence. Nevertheless, supervision from teachers and parents is necessary to prevent this strategy from causing adverse effects in the form of dependence that may harm the psychological development of children. These findings have important implications for educational practice, particularly in designing approaches that promote sustainable independence and self-confidence.